(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2016)
To expand the range of 3-(1,3,4-thiadiazol-2-yl)chromones’ polyfunctionality by introducing carboxyl and amino functions the modificaton of 7-hydroxy-3-(5-phenyl-1,3,4-thiadiazol-2-yl)-6-ethylchromone was carried out. Alkylation of the latter with methyl 2-bromacetate or ethyl 2-chloracetate in dimethyl formamide in the presence of potassium carbonate resulted in methyl or ethyl 2-[6-ethyl-4-оxо-3-(5-phenyl-1,3,4-thiadiazol-2-yl)-4Н-7-chromenyloxy]аcetates. The following hydrolysis of the esters in the mixture of acetic and sulfuric acids led to 2-[6-ethyl-4-оxо-3-(5- phenyl-1,3,4-thiadiazol-2-yl)-4Н-7-chromenyloxy]аcetic acid. The transformation of the resulting acid under action of hydroxylamine hydrochloride was investigated. The action of hydroxylamine hydrochloride in pyridine on 2-[6-ethyl-4-oxo-3-(5-phenyl-1,3,4-thiadiazol-2-yl)-4Н-7-chromenyloxy]acetic acid adduced to opening of γ-pyrone cycle and subsequent cyclization of intermediates іnto isoxazole derivatives, which undergo further ring opening followed by intramolecular reaction of nitrile and hydroxyl groups to form 2-[2-amino-6-ethyl-4-oxo-3-(5-phenyl-1,3,4-thiadiazol-2-yl)-4Н-7-chromenyloxy]acetic acid. These transformations allowed to introduce carboxyl and amino functions into 3-(1,3,4-thiadiazol- 2-yl)chromones, which in turn makes them available for use and allows to extend the spectrum of their application